Media in Education
X, 106 p.
Keywords: Embracing the contribution and active participation of researchers, teachers, creators, managers and other specialists, this volume provides in-depth discussion of: • Students’ perspectives on media in the classroom • Students and media (as content and as tools for learning) • Educational Media Design • Institutional Impact of the integration of Educational Media • Old v. New Media: what really matters? • Research and Evaluation • Personal and/or social learning environments/networks • Media and inclusion • Media and informal learning • Immersive learning environments • Virtual mobility in Education • Mobile learning • Media and literacies The best peer-reviewed and hand selected papers presented at the 2011 ICEM and SIIE Joint Conference in Portugal make up the volume. Taken as a whole, they provide the most up-to-date material published on the future of ICT and the media in education, providing an invaluable resource to researchers, curriculum developers, policy makers, and anyone interested in the latest information about this emerging and exciting area of study.